DETERMINATION OF THE CONTENT OF PHENOLIC COMPOUNDS IN YOGURT EXTRACT (USING THE HPLC METHOD) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In this study, a high-performance liquid chromatography (HPLC) method based on the HPLC technique was developed for the determination of phenolic compounds (salicylic acid, quercetin, apigenin, rutin, gallic acid, and kaempferol) in yogurt extract. Standard solutions were prepared in 96% ethanol using an ultrasonic bath, while the sample was extracted with 96% ethanol at 60°C for 20 minutes, followed by centrifugation and filtration through a 0.45 μm membrane filter. The analysis was performed on a Shimadzu LC-40 Nexera Lite system using a Shim-pack GIST C18 column (150 × 4.6 mm; 5 μm) under gradient elution conditions with acetonitrile and 0.5% acetic acid. The injection volume was set at 10 μL, the flow rate at 0.5 mL/min, the column temperature at 40°C, and detection was carried out at 300 nm. The results indicated that only salicylic acid (11.188 mg/100 g) and quercetin (50.235 mg/100 g) were detected in the sample, while the concentrations of other compounds were below the detection limit. Given its high reproducibility and sensitivity, this method is recommended for the determination of polyphenols in food matrices.